Fenomena Muen Shakai dalam Dua Novel Jepang - Unsriana, Linda (Humaniora, 2015)
On January 31, 2010 NHK (Nippon Hoso Kyokai) reported that 32 thousand people died each year alone and buried by the local government. The news immediately raised the interest of the problem called disconnected society (muen shakai), that Japanese people live in less socializing with relatives or neighbors. This research examined the muen shakai phenomenon in two Japanese novels, Grotesque and Umibe no Kafka. The approach used in this research is sociology of literature, that literature is not only artworks but also real representation of the social state. Descriptive analytical method was used through library study by describing and analyzing data to derive a conclusion. Research found that muen shakai exists in both Grotesque and Umibe no Kafka. The phenomenon is due to changes in Japan?s family system, from Ie to kaku-kazoku.